ANALISIS PENGELOLAAN KESEHATAN LINGKUNGAN RUMAH SAKIT SEBAGAI USAHA PENCEGAHAN INFEKSI NOSOKOMIAL DI RUMAH SAKIT MARTHA FRISKA KELURAHAN BRAYAN KOTA KECAMATAN MEDAN BARAT TAHUN 2014 - Theodora Simatupang; evi naria; surya dharma (Lingkungan dan Kesehatan Kerja, 2014)
The management on a hospital’s environmental should be done in integrated administration controlling all the environmental hospital it. To maintain the hospital’s environment for not properly shall contribute cause an nosocomial infection with many cases resulted in human death. This condition assure how necessary to conduct an analytical research in managing the environmental of hospital with the purpose to prevent any nosokomial infected as held on Martha Friska Hospital of Medan for 2014. The objective of this study is to describe of the management in the hospital environmental of ICU of Martha Friska hospital mainly in order to maintain the existence, how to control, and the attitude of preventing nosocomial infection on the hospital environmental. This study is a descriptive survey research with population are all nurses as paramedic serving on ICU Unit. Total sample 24 respondents. In addition, this research also applied a general guidance in management of hospital’s environmental based on the Ministry of Health’s decree of 1204 for 2004. The results indicated that mostly respondents is noted female in 79.2%. Upon the education level, averagely they got have Diploma degree noted some 91.7%, and no respondents ever got have special coaching or training about naosocomial infection, even any special certificate on it. The management, the internal controlling as done of hospital scope in Martha Friska is classified sufficiently rate based on the Ministry of Health’s decree in 1204 for 2004. It is suggested to the management of hospital kindly provide special coaching in the point to prevent nosocomial infection mainly to on ICU Unit, in order to while serving public be better to nosocomial infection , it shall create health service that give the best quality on patient visiting the hospital. Keywords : Environmental, Nosocomial. Infection , Management.